HEART RATE VARIABILITY AND ARRHYTHMIAS IN PATIENTS WITH END STAGE CHRONIC RENAL FAILURE ON PROGRAMMED HEMODIALYSIS - H. H. Shugushev; M. M. Khamizova; V. M. Vasilenko; Z. H. Shugushev (Российский кардиологический журнал)
The article contains data on the influence of programmed hemodialysis on the structure and incidence of supraventricular and ventricular arrhythmias in patients with end stage chronic renal failure. 67 patients have been studied with the usage of continuous ECG monitoring, assessment of heart rate temporary and spectral parameters before, during and after hemodialysis (n = 48) and in patients with chronic renal failure one the pre-dialysis stage (n = 19). It have been noted that hemodialysis procedures are accompanied by activation of the whole autonomous nervous system with predominant vagus influence on the heart and decreased sympathetic tone. Following hemodialysis the activity of autonomous nervous system is decreased significantly with predominant sympathetic influence on the heart increasing myocardium electric instability. Relationship between changes in heart rate variability and the development of hazardous arrhythmias, as well as with changes in electrolytes concentration, is covered.